Application of high resolution pQCT analysis for the assessment of a bone lesion: A technical note. Issue 1 (January 2015) - Rubinacci, A.; Tresoldi, D.; Villa, I.; Rizzo, G.; Gaudio, D.; De Angelis, D.; Gibelli, D.; Cattaneo, C.
Highlights pQCT helps in gaining a precise reconstruction of lesions within trabecular bone. Elaboration of 3D models helps in estimating the volume of the lack of tissues. The application of pQCT scan is a useful tool for assessment of bone lesions.